An investigation into the principal modes of action of surfactants and how a novel formulation may improve turfgrass quality by increasing the dominance of Agrostis spp. in golf greens. Issue 1 (27th April 2022) - Martin, Thomas; Rothwell, Shane; Stevens, Carly
Abstract: The aim of this study was to establish the mechanisms underpinning the observations made in a field trial that suggested that a novel surfactant treatment could promote bentgrasses ( Agrostis spp.) in golf greens that contain annual meadow grass ( Poa annua L.). Assessments of the effects of three surfactant treatments (named Treatments 1, 2, and 3) on shoot height, biomass accumulation, rhizosheath properties, soil water distribution, and rooting characteristics were made over the course of two experiments carried out under controlled conditions. We found that the leaf extension rate was significantly affected in the two grass species to different extents, depending on the surfactant used. This finding could have positive implications for turf quality in the field for a newly developed formulation (Treatment 3), which was observed to be the case in the field trial that pre‐dated this study. The same treatment also resulted in significant differences in the grasses in terms of rhizosheath size compared with untreated soil. We found that surfactants affected the distribution of water in the soil by increasing the rhizosheath water content to bulk soil water content ratio, potentially maximizing water and nutrient uptake by the roots. The combination of effects observed with use of the novel surfactant treatment may lead to improved water use efficiency and a more desirable sward composition for golf greens. Core Ideas: A novel wetting agent treatment influenced the species composition of golf greens without use of pesticides. We showed that the effects of using wetting agents can extend beyond those relating to water only. The observed effects of a chemical product may differ between plant species. Influencing the formation and water content of the rhizosheath may be an important factor when attempting modification of species composition in a turfgrass stand. The effects of wetting agent treatments may be similar between cut and free‐growing stands of turf.